An analysis of students’ summaries using summary sentence decomposition - Norisma, Idris; Sapiyan, Baba; Rukaini, Abdullah (Centre for Academic Information Services, UNIMAS, 2014)
Summary writing is a process of reducing the size and content of a text into a shorter version called summary. The production of the summary depends on the existing text which is different from other writings such as essay writing and report writing (Hidi & Anderson, 1986). However, it is important to have good summarization skills in order to determine what to include, what to eliminate, how to organize information and how to ensure that the summary retains the meaning of the original text. There are five basic rules that are essential to produce adequate summaries (Brown & Day, 1983):